(untitled) (British Journal of Multidisciplinary and Advanced Studies, 2024)
Youth unemployment is a pressing issue in many regions, including Jigawa State, Nigeria. This study examines the activities of the Ringim Skills Acquisition Center and its impact on reducing youth unemployment in Ringim Local Government Area. Using a mixed-methods approach, the research incorporates both quantitative data from surveys of program participants and qualitative insights from in-depth interviews with center staff and beneficiaries. The findings reveal that the center offers a range of vocational training programs that significantly enhance employability skills among youths. Notably, participants reported increased job opportunities and entrepreneurial ventures following their training. Despite these successes, challenges such as limited funding and inadequate infrastructure were identified as barriers to optimal program delivery. This study underscores the critical role of skills acquisition centers in addressing youth unemployment and provides recommendations for policy enhancement and future research to further improve the efficacy of such programs. The implications for policymakers, educators, and community leaders highlight the need to sustained investment and support to maximize the impact of skills acquisition initiatives.